Increasing collegiate strength and conditioning coaches' communication of training performance and process goals with athletes - Moore, E. W.; Quartiroli, A.; Zakrajsek, R.; Eckenrod, M. (Strength and Conditioning Journal, 2019)
This article presents information about goal setting and how strength and conditioning coaches (sccs) can incorporate goal setting strategies in their athletes' training. The article presents an overview of outcome, performance, and process goals, based on the specific, measurable, aggressive yet achievable, relevant, and time-bound (smaart) framework. Strategies sccs can use are presented to illustrate how to increase the effectiveness of the performance and process goals that informed the program periodization and feedback provided by the scc. This article aims to start bridging the gap between scc familiarity with goal setting and incorporation of this mental strategy into their communication with athletes about training.